Examining Gender Disparities in Computational Archaeology Publications: A Case Study in the Journal of Computational Applications in Archaeology and the Computer Applications and Quantitative Methods in Archaeology Conference Proceedings. - JOHNSON, PHYLLIS S. (Journal of Computer Applications in Archaeology, 2022)
Since the 1970s, archaeologists have begun acknowledging the gender disparities that have long existed within the field of archaeology. This has become especially evident within academic publishing over the past decade as archaeologists have started digging deeper into publishing trends within the field. Following this trend, the present research examines gendered differences in the subfield of Computational Archaeology through the analysis of data from publications in the Journal of Computer Applications in Archaeology (JCAA) and the Computer Applications and Quantitative Methods in Archaeology (CAA) conference proceedings, both of which focus on digital and computational archaeological methods. The results of this study demonstrate that women represent only 25 percent of first authors for the JCAA and 40 percent of first authors for the CAA proceedings. Given these discrepancies, more research is needed to understand why these discrepancies exist and whether parallel differences are present within other publishing outlets, in funding for computational archaeology projects, and within academic hiring.